Kesejahteraan Sejagat: Analisis dari Perspektif Maqasid al-Syariah - Sulong, Jasni; Ismail, Faisal Husen (Jurnal Usuluddin, 2010)
Islam means safe and harmony. The coming of Islam brings safe and harmony towards human kind with legal justice that in line with social needs. In order to ensure the safe and harmony to the community, Islam has established two form of relationships which are the relationship among people with the Creator and the relationship among people themselves. The relationship within people should be based on good deed and bring benefit among them. In this situation, they are neither have a special place to Allah nor have to be treated well except who are obedient and pious. Thus, all human kind is equal to Him and entitled equal rights. Neither oppression nor cruel behaviour is permitted in the relationship among human kind. More over, the same things happened in the relationship with Allah which was based on the benefit of people on the eye of the religion (objective of shariah). This yardstick has put all those value of safe and harmony under Islamic spirit of views for the benefit of all people. Thus, no disagreement and confusion took place in understanding the accurate merit of safe and harmony towards people as it meet the objectives of shariah. Therefore, no wonder both of the relationships that are built between people and Allah as well as between people themselves have manage to benefit humankind in the way of safety and harmony. In this case, Islamic law as the law of samawi (revealed law) become the only law that manage to ensure the justice towards people in this world. Hence, this paper is triggered to discuss on how the function and modus operandi of Islamic law that manage to ensure the safe and harmony. The shariah elements and relevance examples will be also forwarded in this study to clarify further regarding the objectives of shariah in guarantee the safe and harmony among people in this world which then could be understood universally.